Omental Lymphangioma in Adults—Rare Presentation Report of a Case - T. Narayana Rao; T. Parvathi; A. Suvarchala (Case Reports in Surgery)
Lymphangioma is an uncommon benign lesion that usually occurs during childhood. Its occurrence in adults is rare. Its presentation in the abdomen is even rare. This case report describes a case of omental lymphangioma presented as retroperitoneal lump. Subsequent imaging, operative, and histological findings revealed omental lymphangioma. Laparotomy done under general anesthesia, a 10 × 12 cm cystic swelling arising from omentum, identified complete excision of the cyst done and send the specimen for histopathological examination. Biopsy report came as omental lymphangioma. Complete surgical excision is the treatment of choice. Prognosis is excellent and recurrence rate is very low if resection is complete. During two years of followup no recurrence was detected. Omental lymphangioma is very rare presentation among abdominal lymphangiomas specifically in adults. Complete excision is the treatment of choice. Long-term followup is required to detect recurrence.